Elevated Plasma Angiopoietin-2 Levels Are Associated With Fluid Overload, Organ Dysfunction, and Mortality in Human Septic Shock. Issue 11 (November 2016) - Fisher, Jane; Douglas, James J.; Linder, Adam; Boyd, John H.; Walley, Keith R.; Russell, James A.
Abstract : Objectives: Angiopoietins modulate endothelial permeability via endothelial cell junctions. Angiopoietin-2 blocks the angiopoietin-1/Tie-2 interaction that stabilizes these junctions, and elevated plasma angiopoietin-2 levels are associated with vascular leakage. We hypothesized that plasma angiopoietin-1 and angiopoietin-2 levels are associated with indirect markers of increased vascular permeability, organ dysfunction, mortality, and plasma proinflammatory cytokine levels in human septic shock. Design: Multicenter observational cohort study derived from a randomized controlled trial (Vasopressin and Septic Shock Trial of vasopressin versus norepinephrine in septic shock). Setting: ICUs of hospitals in Canada, Australia, and the United States. Patients: Three hundred forty-one patients in the randomized, controlled Vasopressin and Septic Shock Trial trial of vasopressin versus norepinephrine in septic shock. Interventions: None. Measurement and Main Results: We measured plasma levels of angiopoietin-1 and angiopoietin-2 at study baseline and determined their association with percent fluid overload and acute organ dysfunction and generated a receiver operating characteristic curve for plasma angiopoietin-2 levels versus acute kidney injury. We also determined the association of angiopoietin-1 and angiopoietin-2 levels with hemodynamics, mortality, and plasma cytokine levels. Plasma angiopoietin-2 levels were directly associated with percent fluid overload at baseline ( r s = 0.18; p = 0.0008) and at 6 hours ( r s = 0.13; p = 0.023), but not at 24 hours ( r s = 0.041; p = 0.46). Plasma angiopoietin-2 levels were associated with the development of hepatic ( p < 0.0001) and coagulation ( p < 0.0001) dysfunction and acute kidney injury ( p < 0.0001). Receiver operating characteristic curve had an area under the curve of 0.73 for acute kidney injury. angiopoietin-2 levels were also inversely associated with days alive ( r = –0.24; p = 0.010) and positively associated with increased 7-day (log-rank trend chi-square = 5.9; p = 0.015) and 28-day (log-rank chi square = 4.9; p = 0.027) mortality. A threshold of angiopoietin-2 levels above the first quartile (> 5, 807 pg/mL) was observed to be associated with increased mortality risk, which aligns with prior studies. Plasma angiopoietin-2 levels were positively associated with plasma cytokine levels, including tumor necrosis factor-α and interleukin-6 at baseline ( r s = 0.39; p < 0.0001 and r s = 0.51; p < 0.0001) and at 24 hours ( r s = 0.29; p < 0.0001 and r s = 0.41; p < 0.0001). Conclusions: Increased plasma angiopoietin-2 levels are associated with increased fluid overload, hepatic and coagulation dysfunction, acute kidney injury, mortality, and plasma cytokines in human septic shock. angiopoietin-2 activation may increase vascular leakage leading to increased fluid requirements, organ dysfunction, and death from septic shock. Abstract : Supplemental Digital Content is available in the text.